The Contribution of Puputan Margarana Renon Square to the Development of Denpasar as a Sustainable City - Bagus Suryada I Gusti Agung; Bayu Anggawirya Anak Agung Bagus (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
This study examines the role of Puputan Margarana Renon Square in supporting Denpasar’s development as a sustainable city through an urban architectural perspective encompassing urban form, urban structure, and urban function. Using a qualitative-descriptive approach, data were collected through field observations, visual documentation, and a literature review related to sustainable urban development and traditional Balinese architectural principles. The findings show that in terms of urban form, the square features a symmetrical configuration oriented toward the Bajra Sandhi Monument, reflecting the principles of Asta Kosala Kosali and Tri Hita Karana, which strengthen the visual identity and legibility of the city. From a structural perspective, the area comprises three key layers: an ecological structure formed by dense vegetation that functions as a green buffer and water infiltration zone; a circulation structure that supports sustainable mobility through pedestrian pathways and an integrated vehicular network; and a social structure that accommodates diverse community activities, including sports, cultural events, and traditional ceremonies. Functionally, Renon Square contributes to reducing local temperatures, improving air quality, enhancing social interaction, and reinforcing Denpasar’s architectural character. The study concludes that Renon Square is a strategic public space that significantly contributes to the environmental, social, and aesthetic sustainability of Denpasar. Recommendations emphasize strengthening public space management to support future sustainable urban development.